A new European species of Delia Robineau-Desvoidy (Diptera: Anthomyiidae) near the wheat bulb fly, D. coarctata (Fallén) - Michelsen, Verner (Zootaxa, 2007)
A new species of Delia Robineau-Desvoidy is described from Europe (Denmark, Sweden, Finland and Czech Republic) by the name of D. coarctoides. It is very similar to and has been confused with the wheat bulb fly, D. coarctata (Fallén), a well known anthomyiid pest species of cereals and grasses in Europe. A brief overview of the D. coarctata species group and a key to males and females are given.